Model Picture and Picture untuk Meningkatkan Keterampilan Berbicara Sesuai Unggah-ungguh - Bethy Mahara Setyawati (Ideguru: Jurnal Karya Ilmiah Guru, 2021)
The aim of this research is to improve students’ activeness and learning outcome based on Javanese etiquette in Class VIIIB of SMP Negeri 4 Wates. This research is carried out in two cycles, each consisting of planning, action, observation and reflection. The subject of this research is students of Class VIIIB in SMP Negeri 4 Wates, 31 students. The data collection technique uses observation, notes and speaking test based on Javanese etiquette. The research outcome shows students’ activeness improves than before they were given action, cycle 1 and cycle 2. The learning outcome in cycle 1 shows there are 2 students (6%) in very skilled category, 9 students (29%) in skilled category, 7 students (23%) in medium skilled category and 13 students (42%) in less skilled category. In cycle 2, there are 8 students (26%) in very skilled category, 11 students (32%) in skilled category, 2 students (11%) in medium skilled category and 4 students (20%) in less skilled category.